The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1nj05418j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a highly porous three-dimensional PVA/GO/ZIF-67 cryogel for the simultaneous treatment of water contaminated with cadmium(ii) and lead(ii) heavy metal ions

Abstract: In this research, PVA/GO/ZIF-67 cryogel as a highly porous three-dimensional polymeric adsorbent was synthesized by freeze-drying method and applied for the simultaneous removal of Cd2+ and Pb2+ ions from contaminated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…The adsorption capacity follows the order of Cu 2+ > Pb 2+ > Cr 6+ , which is related to the hydrated ionic radii of these metal ions. 58,59 These results confirm that the flexible ZIF-67@ANF aerogel textiles exhibit great potential for adsorption of hazardous pollutants similar to MOF powder materials.…”
Section: Applications Of Zif-67@anf Aerogelsupporting
confidence: 62%
“…The adsorption capacity follows the order of Cu 2+ > Pb 2+ > Cr 6+ , which is related to the hydrated ionic radii of these metal ions. 58,59 These results confirm that the flexible ZIF-67@ANF aerogel textiles exhibit great potential for adsorption of hazardous pollutants similar to MOF powder materials.…”
Section: Applications Of Zif-67@anf Aerogelsupporting
confidence: 62%
“…In addition, the values 20.9 < Δ H ° < 418.4 kJ mol −1 have been attributed to the chemisorption process. 25 Therefore, the results revealed that the adsorption of TA and SY dyes may have occurred with the cooperation of both physical and chemical processes. The positive Δ S 0 values (243.6 J mol −1 K −1 for TA, and 322.2 J mol −1 K −1 for SY) suggest an increase in randomness at the solid–liquid interface during the adsorption process and also some changes may have occurred in the internal structure of the adsorbent through the adsorption.…”
Section: Resultsmentioning
confidence: 96%
“…24 In this regard, ZIF-67 is one of the ZIFs which consists of the Co 2+ metal ion as the metallic node and 2-methylimidazole as the organic ligand and it has been used for various applications like adsorption, separation, electrochemistry, catalysis, and so on. 23 In recent years, ZIF-67 and its composites have been broadly used as a potential adsorbent for the efficient removal of a wide range of pollutants like heavy metal ions, 25 agricultural pesticides, 26 dyes, 27 pharmaceuticals, 28 etc. from contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, traditional adsorbents (i.e., activated carbon and bio-adsorbents) have limited adsorption capacity, and most of them are expensive, which causes the restriction of their large-scale application . Consequently, researchers are dedicated to developing new adsorbents, such as magnetic Fe 3 O 4 /H 2 SO 4 -activated Myrtus Communis leaves carbon, zeolite-based geopolymers, and porous three-dimensional polymerics, for removing these two metal ions from wastewater efficiently and economically. …”
Section: Introductionmentioning
confidence: 99%
“…Wastewater contaminated by heavy metals has drawn increasing concern because of their non-degradation, carcinogenicity, and toxicity . Typically, excessive cadmium (Cd 2+ ) and lead (Pb 2+ ) cause depression and cancerization of the cardiovascular system, neurological system, and reproductive system in the human or animal body. , The World Health Organization (WHO) has specified the maximum permissible limit of Cd 2+ (0.15 mg·L –1 ) and Pb 2+ (0.10 mg·L –1 ) in drinking water .…”
Section: Introductionmentioning
confidence: 99%